Efektifitas Bimbingan Kelompok dengan Metode Halaqah untuk Meningkatkan Authentic Happiness - Yogi Damai Syaputra; Ajril Mustaqim; Hanifatun Nisa; Monalisa; Mohamad Thohir (DA'WA: Jurnal Sosial dan Dakwah, 2025)
This study aims to measure the level of authentic happiness of students and to test whether group guidance with the halaqah method is effective in increasing authentic happiness. The study used a true experimental design with the Solomon Four-Group Design. The sample in this study was as many as 60 respondents, who were divided into four groups of 15 respondents from Islamic counseling and Islamic education counseling students. This research instrument used the Authentic Happiness Scale, which consisted of 23 valid statement items and a reliability of 0.870. The results of the study showed that the average authentic happiness was in the less happy category. After being given an intervention, authentic happiness increased to the happy category. The results of the study also showed that there was a difference in the authentic happiness of students in the experimental and control groups after being given a group guidance intervention with the halaqah method by controlling the initial ability of happiness. Then, the results of the study also showed that there was a difference in the authentic happiness of students in the experimental and control groups after being given a group guidance intervention with the Halaqoh method. So, it can be concluded that group guidance with the halaqah method is effective in increasing happiness.